MAPPING OF PROTO VILLAGE COMMUNITY HEALTH CONDITIONS KEDUNGWUNI SUB-DISTRICT, PEKALONGAN DISTRICT - Maulia, Rizka; Piranti, Agatha Sih; Aji, Budi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
A person's level of health is influenced by four factors, namely, heredity, environment, behavior and health services, where environmental factors have the greatest role. In Proto Village, based on data from the Village Health Polyclinic, most environmental-based diseases were found, such as ISPA, diarrhea and skin diseases. Information on the distribution of disease in Proto Village can be done using Geographic Information System (GIS) technology in the form of a thematic maps. This research aims to map the distribution of environmental-based diseases in Proto Village with a Geographic Information System (GIS) approach. The type of research is qualitative, case study design with a Geographic Information Systems (GIS) approach. The research location is in Proto Village, Kec. Kedungwuni, Kab. Banjarnegara. The research was conducted in August 2021 - August 2022. The research instruments were GIS software, data on the health conditions of the Proto Village community. Descriptive data analysis methods overlay techniques and scoring techniques. Based on the results of the disease distribution mapping analysis, two RWs in Proto Village are in vulnerable status, namely RW 2 and RW 3, while RW 1 is not in vulnerable status. The distribution pattern of ARI diseases is clustered in RW 3 and random in RW 1 and RW 2. The distribution pattern of diarrhea disease is random, while the distribution pattern of skin diseases is clustered. Based on the condition of well water quality, ARI disease is not caused by water quality, viruses, dust, lack of open ventilation. Diarrhea is caused by water quality and climate change, while skin disease is caused by water quality, personal hygiene, overcrowding and lack of ventilation.